Exercise-induced neurogenesis through BDNF-TrkB pathway: implications for neurodegenerative disorders - Lee Jun Jie; Sitjar Patrick Henry Sebastian; Ang Eng Tat; Goh Jorming (Translational Exercise Biomedicine)
Current scientific endeavours in the field of geroscience have begun to reveal how factors such as exercise could modulate the brain aging process. In this review, we ask how exercise could potentially modulate aging, and by extension, the development of Alzheimer’s Disease (AD). Furthermore, we discuss how exercise could mitigate the cascade of debilitating manifestations in AD. Mechanistically, we discuss how biomolecules such as brain-derived neurotrophic factor (BDNF) and its cognate receptor, tropomyosin receptor kinase B (TrkB) could change during the life course and how its signalling pathways could be altered with exercise (acute sessions or chronic training). Tackling these questions could help the scientific and medical community mitigate age-related decline in terms of neurological functions.